Design of Prototype for Metal Detecting Arduino Mobile Robot using Wireless Sensor Network Powered by Solar Energy - Raman, Jeyagopi; Choon, Kit Chan; Kar, Manoj Kumar; Gupta, Munish Kumar; Baskara, Sudesh Nair; Kaewthep, Chaloemphol (Journal of Advanced Research Design, 2025)
In today’s modern technology world, there are several types of mobile robots which use different types of renewable energy systems. The advancement of modern technologies is increasing energy demand volume and is aimed at adopting alternative sources of energy. Renewable energy systems, such as solar power are the better choice to use in moving mobile robots. Robots are the fast-growing technology and communication mode to human in daily lives. Therefore, researchers have integrated solar power as an alternative energy source on mobile robots, which will solve the depletion of fossil fuels. Thus, a four wheels’ metal detection solar powered mobile robot was designed in these studies. The mobile robot is implemented using solar panels, Arduino Uno, metal detector sensor and solar power. The Android Uno was implemented in the development of this mobile robot as its primary brain and to communicate with all its components. In these studies, solar power metal detecting mobile robot is developed to detect the metal and the mobile robot is powered by solar energy and the robot control via wireless sensors network controller. Studies were also done on solar panel testing with various atmospheres and temperatures to accustom the product. The automated robot and the proposed design are compared in terms of the mobile robot’s accessibility, metal detecting accuracy and stability of power source. The findings demonstrate that the mobile robot’s proposed design can deliver faster metal detection with a more precise, easier in turning and highly dependable power supply.